Insulin resistance and impaired glucose tolerance in overweight and obese Costa Rican schoolchildren - Holst Schumacher, Ileana (2008)
Background. Worldwide obesity has become an unprecedented public health challenge. In addition, a notable increase in the risk of insulin resistance and type 2 diabetes mellitus has emerged. In Costa Rica, there are no epidemiological data to establish the prevalence of type 2 diabetes in the pediatric population. However, information from the Endocrinology Department of the Children’s National Hospital indicates an increased number of cases in the last 2 to 3 years. Objective. To determine the prevalence of insulin resistance and impaired glucose tolerance in overweight and obese schoolchildren. Methods. This cross-sectional study was conducted among 214 healthy 8- to 10-year-old children from urban schools of San José, Costa Rica. Anthropometric measurements and blood determinations of glucose, insulin, proinsulin, glycosylated hemoglobin, C-peptide, and leptin were performed. Indexes were calculated to assess insulin resistance. Information on social and lifestyle variables was obtained from questionnaires, and acanthosis nigricans was certified by a physician. Statistical analysis was performed with SPSS software for Windows, version 10.0. Results. The prevalence of type 2 diabetes mellitus was very low (0.5%) in the studied population. However, hyperinsulinemia and impaired glucose tolerance were present in 20.6% and 6.5% of the subjects, respectively. On the basis of the Fasting Glucose-to-Insulin Resistance Ratio (FGIR), 46.7% of the children showed insulin resistance. Girls and obese children (body mass index ≥ 95th percentile) were more likely to have higher serum insulin levels and insulin resistance than boys and overweight children (BMI ≥ 85th percentile). Compared with the lowest quintile, children in the highest quintile of body-fat tissue had higher insulin resistance but had similar serum concentrations of glucose, C-peptide, and proinsulin. Positive family histories of type 2 diabetes mellitus and sedentarism (73.7% and 40.7%, respectively) were highly prevalent among overweight and obese children. Conclusions. The prevalence of impaired glucose tolerance and insulin resistance in obese children indicates a worrisome trend in the incidence of type 2 diabetes in Costa Rica. Strategies for weight reduction, obesity prevention, and promotion of healthy lifestyles are necessary to prevent the onset of type 2 diabetes during childhood and adolescence.